KINERJA KARYAWAN TIGA SUB-SEKTOR INDUSTRI KREATIF YANG DIPENGARUHI KEMAMPUAN DAN PERILAKU KERJA DI SURABAYA - asjari, fachrudy (Majalah Ekonomi, 2016)
Abstract Background. This research intended to asses the ability and work behavior which must be performed by three sub-sector in creative industry in Surabaya connected with performance of the employee. Method. This research was conducted at by three sub-sector in creative industry in Surabaya which covered 170 employee as respondent. This research by utilizing Regression, the technique was processed with SPSS program 23 to analyze some hypothesis. The intercorrelations models between these variables in this study revealed that three hypothesis have significant correlation. Conclusion. The result of this research were empirical date of the development of the theoretical of human resources and practice management. Key words. Ability, Work Behavior and Performance.